2022
DOI: 10.1038/s41598-022-12191-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein Grp78/BiP/HspA5 binds directly to TDP-43 and mitigates toxicity associated with disease pathology

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with no cure or effective treatment in which TAR DNA Binding Protein of 43 kDa (TDP-43) abnormally accumulates into misfolded protein aggregates in affected neurons. It is widely accepted that protein misfolding and aggregation promotes proteotoxic stress. The molecular chaperones are a primary line of defense against proteotoxic stress, and there has been long-standing interest in understanding the relationship between chaperones and agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…Network analysis also revealed an association of a set of endoplasmic reticulum enriched proteins with disability progression rate, in particular: Endoplasmic reticulum chaperone BiP (HSPA5, BiP or GRP78), calreticulin (CALR), and protein disulfide isomerase 4 (PDIA4), which are all associated with induction of endoplasmic reticulum stress. Endoplasmic reticulum stress is thought to be an important early factor in cellular dysfunction in both sporadic and C9orf72 ALS, with a direct interaction between TDP‐43 and BiP also demonstrated (Dafinca et al., 2016, 2021; Feneberg et al., 2020; François‐Moutal et al., 2022; Pilotto et al., 2022; Sasaki, 2010). Our study therefore provides additional novel data indicating a signature of this endoplasmic reticulum dysfunction is evident in CSF, which may be of importance in understanding prognostic heterogeneity in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Network analysis also revealed an association of a set of endoplasmic reticulum enriched proteins with disability progression rate, in particular: Endoplasmic reticulum chaperone BiP (HSPA5, BiP or GRP78), calreticulin (CALR), and protein disulfide isomerase 4 (PDIA4), which are all associated with induction of endoplasmic reticulum stress. Endoplasmic reticulum stress is thought to be an important early factor in cellular dysfunction in both sporadic and C9orf72 ALS, with a direct interaction between TDP‐43 and BiP also demonstrated (Dafinca et al., 2016, 2021; Feneberg et al., 2020; François‐Moutal et al., 2022; Pilotto et al., 2022; Sasaki, 2010). Our study therefore provides additional novel data indicating a signature of this endoplasmic reticulum dysfunction is evident in CSF, which may be of importance in understanding prognostic heterogeneity in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…However, BiP positivity was not correlated with Ki67 index and did not significantly change after treatment, although its subcellular localization was significantly increased in the nucleus. BiP can be directed to the nucleus [ 62 ] where it may play a role in reducing DNA damage-induced apoptosis [ 63 , 64 ], while in amyotrophic lateral sclerosis, it binds to TDP-43 to prevent its misfolding and subsequent toxicity [ 65 ]. Moreover, BiP was shown to molecularly interact with ERα and to be required for gene transcription in the uterus, serving as a hub between ERα-independent and ERα-dependent estrogenic responses [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used Drosophila to assess sleep in protein expression models of human neurodegenerative disease. We found that directed expression of TDP-43, which is an established model for ALS/FTD (24,47,(54)(55)(56)(57), led to severe sleep deficits. Depletion of Ataxin-2 (Atx2), a modifier of TDP-43 toxicity in flies and mice (45,58,59), reversed the TDP-43 sleep phenotype.…”
Section: Introductionmentioning
confidence: 93%